Relationship Between General Health and Demographic Characteristics of Family Caregivers of Stroke Survivors - Mahboobeh Tajvidi; Asghar Dalvandi; Robab Sahaf; Mehdi Rahgozar (University of Social Welfare & Rehabilitation Sciences, 2018)
Objectives Caregiving of stroke survivors leads to several physiopsychlogical problems for family caregiver due to excessive demand by the stroke survivors. The aim of this study was to determine general health of the caregivers of stroke survivors and their relationship with demographic factors. Methods & Materials This was a cross-sectional study in which 60 caregivers of stroke survivors were selected by convenience sampling from Sina and Firouzgar Hospitals in Tehran province in Iran, in 2015. The data was collected by two questionnaires including demographic questionnaire and General Health Questionnaire (GHQ). The collected data were analyzed by descriptive and inferential statistics including mean and standard deviation using SPSS software (version 15). Results The mean GHQ score was 61.41±14.9; in female caregiver, it was 63.07±16.09, and in male caregiver, the score was 58.33±12.28. Significant correlation found between overall GHQ score and either of the factors such as occupational status, age category, or type of caring (P=0.01). Unemployment in caregiver, aging, and 24-hour caring of stroke survivors were related to a reduction in GHQ score. However, there was no significant association between GHQ of stroke caregivers and either of the factors such as sex (P=0.35), time of caring (0.24), marital status (P=0.71), or educational status. Conclusion This study showed that family caregivers of stroke survivors experience deterioration of general health at different dimensions. Therefore, it is recommended that planning for general health and social support for caregivers should be done through policy making in health and treatment.